2017
DOI: 10.1007/s10815-017-1027-y
|View full text |Cite
|
Sign up to set email alerts
|

CoQ10 increases mitochondrial mass and polarization, ATP and Oct4 potency levels, and bovine oocyte MII during IVM while decreasing AMPK activity and oocyte death

Abstract: The data suggest that CoQ10 improves mitochondrial function in IVM where unwanted stress, higher AMPK activity, and Oct4 potency loss are induced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
27
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 80 publications
(109 reference statements)
4
27
1
Order By: Relevance
“…The supplementation with CoQ10 to the IVM medium failed to increase not only maturation but also fertilization rates and the subsequent embryo development. These results are in disagreement with those reported in bovine, where CoQ10 treatment for 24 hr of maturation increased oocyte survival and the percentage of oocytes achieving the MII stage compared with control oocytes (Abdulhasan et al., ). These authors indicated that the improved conditions of maturation in vitro counteracted oxidative stress and that the CoQ10 increased ATP production and decreased AMPK activity, which improved maturation outcomes.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…The supplementation with CoQ10 to the IVM medium failed to increase not only maturation but also fertilization rates and the subsequent embryo development. These results are in disagreement with those reported in bovine, where CoQ10 treatment for 24 hr of maturation increased oocyte survival and the percentage of oocytes achieving the MII stage compared with control oocytes (Abdulhasan et al., ). These authors indicated that the improved conditions of maturation in vitro counteracted oxidative stress and that the CoQ10 increased ATP production and decreased AMPK activity, which improved maturation outcomes.…”
Section: Discussioncontrasting
confidence: 94%
“…The coenzyme Q10 (CoQ10) is an essential cofactor of the electron transport chain present especially within the inner mitochondrial membrane where it serves as a potent antioxidant playing a critical role in protecting the cell in question against mitochondrial dysfunction mediated by oxidative stress (Hernández‐Camacho, Bernier, López‐Lluch, & Navas, ). In addition, CoQ10 promotes the synthesis of adenosine triphosphate (ATP), thus playing a crucial role in the activation of the fertilized oocyte towards further embryo development (Abdulhasan et al., ) owing to the fact that the mitochondria of the zygote are all derived from the oocyte and thus constitute the major source of ATP during the development of the pre‐implantation embryos (Babayev & Seli, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of MitoTracker staining revealed that diffused pattern of mitochondrial distribution, as well as mitochondrial mass, were more pronounced in matured oocytes upon treatment with 30 µM CoQ10. Furthermore, the results of JC1 staining suggested an improvement in mitochondrial membrane potential upon supplementation with 30 µM CoQ10 Which were consistent to previous reports (Abdulhasan et al, ; Gendelman & Roth, ; Liang, Niu, Shin, & Cui, ).…”
Section: Discussionsupporting
confidence: 91%
“…of JC1 staining suggested an improvement in mitochondrial membrane potential upon supplementation with 30 µM CoQ10 Which were consistent to previous reports(Abdulhasan et al, 2017;Gendelman & Roth, 2012;Liang, Niu, Shin, & Cui, 2017).Beside its role in the maintenance of cellular energy, mitochondria contributes to proper chromosomal segregation. This takes place during meiotic divisions and after oocyte activation by sperm(Eichenlaub-Ritter, Vogt, Yin, & Gosden, 2004).…”
supporting
confidence: 91%